Daily and seasonal variation in water relations of macchia shrubs and trees in France (Montpellier) and Turkey (Antalya) - Duhme, F.; Hinckley, T. M. (Vegetatio, 1992)
Based upon two different research studies in the mediterranean regions of France and Turkey, drought resistance strategies were investigated in a broad group of species. The diurnal and seasonal patterns of the water relations of different lifeforms from the thermo-mediterranean to submediterranean lifezones were compared. Three sites near Montpellier, in Southern France, and five sites near Antalya, Turkey were used for this comparison. Xylem pressure potential and relative stomatal aperture were the key water relations parameters collected in France while these parameters as well as osmotic potential and leaf conductance were studied in Turkey. From the 26 different study species investigated in France, 7 distinct types of stomatal control were observed, with the deciduous lifeforms showing the least control, the sclerophyllous and coniferous evergreens the greatest control and the malacophyllous shrublets intermediate levels of control. Predawn water potential values provided a means of classifying species according to their temporal and spatial utilization of site water reserves. The comparison of turgor potentials (difference between water and osmotic potentials) gave an insight into leaf adaptations to site moisture. Species with high predawn water potentials generally maintain positive turgor even at midday during the summer, whereas species with low predawn values were frequently at zero turgor even at predawn. Phlomis grandiJtora was the most extreme species with mid-summer predawns and midday water potentials of -6 MPa and osmotic potentials never more negative than -2.4 MPa.
Keywords: Drought resistance; Malacophyllous shrubs; Osmotic potential; Stomata control types; Turgor loss point; Xylem water potential